Pembentukan Budaya Keagamaan di Lembaga Pendidikan - Bani Bani (LP3M STITNU AL HIKMAH MOJOKERTO, 2019)
In religion, chastened individual and respondent for everlastingly point out affection and mutually please help fellow being squire. Consciousness excelsior gets excelsior religion too sensed affection and push to help help fellow being squire. Religions appreciative instilling constitute important thing is done in an education institute. Religions appreciative instilling constitute unique thing again pulls since deep instilling assess religion exist correlation among educator and participant is taught. Whereabouts in such event, educator not only functions as instructor only, but also as spiritual father for participant to teach, namely as father or commisioned oldster leads, lead and imbeds dogma to its child.